Oligocene-Neogene tectonics and sedimentation in the forearc of southern Peru, Tacna area (17.5°-18.5°5) - Flores, Alexander (2005)
Fault systems observed in the southernmost Peruvian forearc (Tacna area) provide information on the structure of the inner Bolivian Orocline (Arica elbow). Here we present the characteristics of the main fault systems observed in the Tacna area, as well as evidences of structural control on the deposition of Upper Cenozoic units and regional geoforms. We propose a synthetic chronology of deformation.